Improvement of HIV-associated neurocognitive disorders after antiretroviral therapy intensification: the Neuro+3 study. (12th November 2020) - Force, Gilles; Ghout, Idir; Ropers, Jacques; Carcelain, Guislaine; Marigot-Outtandy, Dhiba; Hahn, Valérie; Darchy, Natacha; Defferriere, Hélène; Bouaziz-Amar, Elodie; Carlier, Robert; Dorgham, Karim; Callebert, Jacques; et al.
Abstract: Objectives: Despite the effectiveness of antiretroviral (ARV) therapy to control HIV infection, HIV-associated neurocognitive disorders (HAND) remain frequent. The Neuro+3 study assessed the cognitive improvement associated with ARV intensification based on increased CNS penetration effectiveness (CPE) scoring ≥+3 and total CPE score ≥9. Methods: Thirty-one patients, aged 18–65 years, with confirmed diagnosis of HAND and effective ARV therapy were included. The cognitive improvement was measured using Frascati three-stage classification and global deficit score (GDS) after 48 and 96 weeks of ARV intensification. Ultrasensitive HIV-RNA, neopterin, soluble CD14, CCL2, CXCL10, IL6, IL8 and NF-L were measured in plasma and cerebrospinal fluid at Day 0 (baseline), Week 48 (W48) and W96. Results: The intensified ARV was associated with a median (IQR) CPE score increase from 6 (4–7) at baseline to 10 (9–11). From baseline to W96, the median (IQR) GDS decreased from 1.4 (0.8–2.2) to 1.0 (0.6–2.0) ( P  = 0.009); HAND classification improved from 2 to 1 HIV-associated dementia, 22 to 8 mild neurocognitive disorders, 7 to 17 asymptomatic neurocognitive impairment and 0 to 5 patients without any neurocognitive alterations ( P  = 0.001). In multivariable linear regression analysis, GDS improvement at W96 was significantly associated with CPE score ≥9 after intensification ( P  = 0.014), CD4 lymphocyte increase at W48 ( P  < 0.001) and plasma CXCL10 decrease at W96 ( P  = 0.001). Conclusions: In patients with HAND, a significant cognitive improvement was observed after the ARV intensification strategy, with a higher CPE score. Cognitive improvement was more often observed in the case of a switch of two drug classes, arguing for better control of CNS HIV immune activation.